Holler of the fireflies eaudiobook - Moore, David Barclay (Listening Library, 2022)
A boy from the hood in Brooklyn travels to a STEM camp in an Appalachian holler for one epic, life-changing summer in this brilliant novel from the award-winning author of The Stars Beneath Our Feet. Javari knew that West Virginia would be different from his home in Bushwick, Brooklyn. But his first day at STEM Camp in a little Appalachian town is still a shock. Though run-ins with the police are just the same here. Not good. Javari will learn a lot about science, tech, engineering, and math at camp. And also about rich people, racism, and hidden agendas. But it’s Cricket, a local boy, budding activist, and occasional thief, who will show him a different side of the holler—and blow his mind wide open. Javari is about to have that summer. Where everything gets messy and complicated and confusing . . . and you wouldn’t want it any other way. J + C + summer = ∞